Predictive Factors Of Peer And Educator Involvement On Special Needs Development: Faktor Prediktif Keterlibatan Teman Sebaya Dan Pendidik Pada Perkembangan Berkebutuhan Khusus - Subli Subli; Agus Basuki (Academia Open, 2026)
General Background Education constitutes a fundamental right that demands an environment of inclusive learning catering to the diverse capabilities of all populations. Specific Background Within these settings, cultural arts instruction taught collaboratively provides valuable opportunities for marginalized individuals to acquire communication, creativity, and social competencies. Knowledge Gap Despite known advantages, prior literature predominantly investigates general pedagogical methods, rarely examining the concurrent variables of educator roles alongside peer participation within collaborative artistic frameworks. Aims This quantitative ex post facto study investigates the joint predictive value of teacher facilitation and student involvement concerning the cognitive, social, emotional, and autonomy milestones of marginalized populations. Results Multiple linear regression analysis of observational and questionnaire data from an integrated junior high school demonstrates that both independent variables concurrently account for 77.3 percent of the statistical variance in developmental progression. Crucially, peer participation emerged as the most dominant predictive variable. Novelty This research uniquely isolates collaborative artistic pedagogy as a distinct domain where non-authoritative interactions supersede traditional authoritative facilitation in predicting holistic growth. Implications Schools must prioritize structured cooperative models and peer-tutoring programs over purely authoritative pedagogies, ensuring comprehensive progression. Highlights Active participation from classmates accounts for the most significant portion of holistic growth within integrated classrooms. Classroom facilitators successfully accommodate learner independence through adaptive and cooperative guidance strategies. Cooperative cultural groupwork explains substantial statistical variance concerning overall cognitive and emotional milestones. Keywords Inclusive Education; Cultural Arts; Collaborative Pedagogy; Social Competence; Holistic Growth